Etiology of Upper Gastrointestinal Bleeding: A Five-Year Study at a Tertiary Hospital - Virly Nanda Muzellina; Liovicinie Andarini; Ari Fahrial Syam (The Indonesian Society for Digestive Endoscopy, 2026)
Background: Upper Gastrointestinal bleeding is a common medical condition requiring prompt treatment and endoscopic evaluation. Identifying the causes is crucial for enhancing patient outcomes and guiding clinical decisions. This study aims to evaluate the etiologies of hematemesis and melena over the past five years.Methods: This study analyzed patient records retrospectively who underwent upper gastrointestinal endoscopy at the Gastrointestinal Endoscopy Center in Cipto Mangunkusumo Hospital, Jakarta, Indonesia between 2019 and 2023. Statistical analysis was performed using SPSS version 26.0.Results: Between 2019 and 2023, 5,721 patients underwent upper gastrointestinal endoscopy, with 1,090 (19.1%) due to upper gastrointestinal bleeding. Among these, 593 were male (54.4%) and 497 were female (45.6%), with a mean age of 54.4 ± 15.12 years. The largest age group affected was 40-59 years, comprising 451 cases (41.4%). Of the 1,090 patients, 262 (24%) presented with hematemesis, 654 (60%) with melena, and 174 (16%) with both symptoms. Non-variceal bleeding was identified in 913 cases (83.8%), while variceal causes accounted for 177 cases (16.2%). Erosive gastritis was the leading cause of upper GI bleeding (408 cases, 37.4%), followed by peptic ulcers (270 cases, 24.8%). Among peptic ulcer cases, 136 (50.4%) were located in the stomach. Additionally, cancer was a cause in 104 cases (9.5%), with duodenal cancer being the most common (48 cases, 46.2%).Conclusion: This study identified erosive gastritis as the leading cause of upper gastrointestinal bleeding, followed by peptic ulcers and varices.